Pentingnya Bermadzhab dan Larangan Fanatisme Menurut Pandangan KH. Hasyim Asy’ari - Abidin, Mohamad Zaenal (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2020)
K.H. Hasyim Ash'ari was a great scholar in the 19th century from Java. He was known not only as a cleric figure and founder of the largest organization in Indonesia and even in the world of NU (Nahdlotul Ulama), but more than that he was also known as a National Hero whose first President Ir Soekarno had established him as one of the national heroes that was worth remembering - one of the most famous services in building the independence of the Indonesian people is through his fatwa on the Resolution of Jihad. The important concept of bermadzhab in his view is the result of dialectical life in solving the multidimensional crisis problems experienced by Muslims especially in Indonesia-hejaz. Namely the existence of differentiation between religious groups, including schools in Islamic law. So this thought seeks to offer the concepts of diligence, doctrine and imitate. Thinking about the importance of adamab in his books